2014
DOI: 10.1021/jp5062573
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Photoelectrochemical Properties of an Ir-Doped SrTiO3 Photocatalyst

Abstract: The effect of iridium valence in Ir:SrTiO3 on the electronic structure and the photocatalytic activity in a water splitting reaction was studied. Epitaxial thin film photoelectrodes were grown with controlled Ir valence and used to measure the electrochemical efficiency of Ir:SrTiO3. The positions of the in-gap Ir impurity levels were determined by optical and X-ray photoelectron spectroscopies. Comparison with ab initio calculations was used to assign the observed electronic states to either Ir4+ or Ir3+ dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 44 publications
2
50
0
1
Order By: Relevance
“…In general, trivalent and tetravalent Rh and Ir species are doped at the Ti 4+ , Nb 5+ and Ta 5+ sites in metal oxide materials. [20][21][22][23][24][25]37,38 Among the species, Rh 3+ and Ir 3+ contribute to the visible light response for metal oxide photocatalysts. 20,24,37,38 Sb 5+ was codoped with Rh 3+ at the Ti 4+ and Nb 5+ sites for charge compensation to enhance the formation of Rh 3+ and Ir 3+ and suppress the formation of Rh 4+ and Ir 4+ as efficient recombination centers between photogenerated electrons and holes, while Ba 2+ and La 3+ were replaced at the alkali and alkaline earth metal sites for the same purpose.…”
Section: Preparation Of An Rgo-metal Oxide Compositementioning
confidence: 99%
“…In general, trivalent and tetravalent Rh and Ir species are doped at the Ti 4+ , Nb 5+ and Ta 5+ sites in metal oxide materials. [20][21][22][23][24][25]37,38 Among the species, Rh 3+ and Ir 3+ contribute to the visible light response for metal oxide photocatalysts. 20,24,37,38 Sb 5+ was codoped with Rh 3+ at the Ti 4+ and Nb 5+ sites for charge compensation to enhance the formation of Rh 3+ and Ir 3+ and suppress the formation of Rh 4+ and Ir 4+ as efficient recombination centers between photogenerated electrons and holes, while Ba 2+ and La 3+ were replaced at the alkali and alkaline earth metal sites for the same purpose.…”
Section: Preparation Of An Rgo-metal Oxide Compositementioning
confidence: 99%
“…To improve the photocatalytic efficiency, the band gap of NaNbO 3 has to be reduced with respect to the HEP and OEP. Doping a semiconductor with metals or nonmetals is one of the most effective strategies to adjust its band structure to expand the range of optical adsorption towards the visible‐light region. Choo and Paul prepared a framework composition of Ru‐doped NaNbO 3 , which had an optical band gap of 2.3 eV and showed superior visible photocatalytic performance .…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Although several previous studies indicated that cubic NaNbO 3 with al ayered perovskite structure exhibited highera ctivity in photocatalytic H 2 generation than the other phases, [28][29][30][31][32][33][34] the wide band gap for cubic NaNbO 3 of 3.29 eV [32] limits the photocatalytic efficiencyi nt he visible-light region. To improvet he photocatalytic efficiency,t he band gap of NaNbO 3 has to be reduced with respect to the HEP and OEP.D oping as emiconductor with metals [35][36][37][38][39] or nonmetals [40][41][42][43] is one of the most effective strategies to adjust its band structure to expand the range of optical adsorption towards the visible-light region. Choo and Paul prepared aframework composition of Ru-doped NaNbO 3 ,w hich had an optical band gap of 2.3 eV and showed superior visible photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…9 Several strategies have been proposed to extend its optical absorption edge to the visible (vis) light region, which possesses 43% of the solar energy, through modifying the energy band structure of STO. Doping with foreign atoms, [10][11][12][13][14][15][16][17][18] depositing noble metal, 19 integrating with other materials [20][21][22][23] have been demonstrated to be effective methods to enhance the photocatalytic performance of STO. In the photocatalytic process, the charge carrier recombination occurs within nanoseconds.…”
Section: Introductionmentioning
confidence: 99%